The Role of Professional Learning in Addressing Global Challenges: Tensions and Innovations Associated With AMR - Littlejohn, Allison; Charitonos, Koula; Kaatrakoski, Heli (Frontiers in Education, 2019)
Changing work practice is critical when addressing global challenges. The expansion of work is mediated by a range of tensions inherent in the complex systems within which global challenges exist. This study examines tensions that inhibit the expansion of work practices contextualized within the global health challenge of Antimicrobial Resistance (AMR). The study traces how an AMR surveillance system is being set up in a low-to-middle-income country in Asia (Country A). The research identifies a range of tensions that need to be considered when designing technology-enhanced learning interventions for professionals. This study is significant in moving technology-enhanced learning toward a wholistic approach that takes into account the work environment. This research takes an original standpoint by placing attention on specific work practices, then examining how technology-supported activities can build capacity. This places professionals at the center of a critical approach examining the ways technologies can add value to their professional lives. This work highlights the importance of professionals' “voice” as a lens through which researchers document their reality. The study calls for a fundamental shift in the orientation of technology-enhanced learning interventions, moving attention toward work practice and mapping supporting technologies around this, rather than focusing primarily on the technology and planning learning activity with technology tools.